2009
DOI: 10.1590/s0100-06832009000600035
|View full text |Cite
|
Sign up to set email alerts
|

CO2, CH4 and N2O fluxes in an Ultisol treated with sewage sludge and cultivated with castor bean

Abstract: Organic residue application into soil alter the emission of gases to atmosphere and CO 2 , CH 4 , N 2 O may contribute to increase the greenhouse effect. This experiment was carried out in a restoration area on a dystrophic Ultisol (PVAd) to quantify greenhouse gas (GHG) emissions from soil under castor bean cultivation, treated with sewage sludge (SS) or mineral fertilizer. The following treatments were tested: control without N; FertMin = mineral fertilizer; SS5 = 5 t ha -1 SS (37.5 kg ha -1 N); SS10 = 10 t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 25 publications
0
2
0
1
Order By: Relevance
“…Esta situação representa risco ambiental, pois o aumento gradual da capacidade do solo em fornecer N (Jin et al, 2011) deve, teoricamente, ser acompanhado da redução nas doses aplicadas, para prevenir o excesso de N inorgânico, a lixiviação de NO 3 -para águas subterrâneas (Medaile et al, 1994;Oliveira et al, 2001;Dynia et al, 2006) e a emissão de N 2 O para a atmosfera (Chiaradia et al, 2009;Pitombo, 2011).…”
Section: Introductionunclassified
“…Esta situação representa risco ambiental, pois o aumento gradual da capacidade do solo em fornecer N (Jin et al, 2011) deve, teoricamente, ser acompanhado da redução nas doses aplicadas, para prevenir o excesso de N inorgânico, a lixiviação de NO 3 -para águas subterrâneas (Medaile et al, 1994;Oliveira et al, 2001;Dynia et al, 2006) e a emissão de N 2 O para a atmosfera (Chiaradia et al, 2009;Pitombo, 2011).…”
Section: Introductionunclassified
“…Then, applications of sewage sludge were in 15 May, 2009, 16 April, 2010, 14 April, 2011, and 28 April, 2012 The sewage sludge was distributed on the whole soil surface of each column, and incorporated at the first 10 cm deep, avoiding the soil revolving for the deepest layers. Considering the content of N found in the sludge and 28% of mineralization rate -in kg ha -1 -in the first year after application (Chiaradia et al, 2009) The ammonium sulphate was added to each lysimeter during the first application of sewage sludge and about four months after, at doses about 188 and 97 kg ha -1 . The potassium chloride was also added to each lysimeter during the first application, according to doses of sewage sludge as follows: 177, 132, 87 and 0 kg ha -1 for doses 0, 11, 22 and 44 Mg ha -1 .…”
Section: Methodsmentioning
confidence: 99%
“…A few studies have reported the effects of SS fertilization on the levels of heavy metals in the soil and castor bean plant, but only related to the applied doses of the sludge (CHIARADIA et al, 2009;CAVALCANTI et al, 2015;NASCIMENTO et al, 2015). However, it is also important to study the processes of SS stabilization and their respective effects on the levels of heavy metals in the soil and castor bean plant.…”
Section: Introductionmentioning
confidence: 99%